Self-Confidence Moderates The Effect of Basic Accounting, Mathematics Learning Outcomes, and Learning Behaviour on Accounting Understanding - Andriani, Jane; Listiadi, Agung (Economic Education Analysis Journal, 2021)
This research, aims to analyze the influence of accounting abilities, learning outcomes of mathematics, and learning behaviour towards the level understanding of accounting partially and self confidence can moderate the relationship between basic accounting abilities, learning outcomes of mathematics, and learning behaviour towards the understanding of accounting partially. The respondent of this research were 105 tenthgrade accounting students with probability sampling techniques. Data analysis techniques using software warpPLS 6.0 with the results of research shows that: (1) not related basic accounting ability and learning behaviour with the level of accounting understanding partially (2) there is an influence beetween learning outcomes of mathematics with undesrstanding of accounting (3) self-confidence is not a moderating variable between basic accounting abilities, learning outcomes of mathematics, and learning behaviour towards the level of accounting understanding partially.Suggestions for next research can use other aspects related to comprehenssion of accounting other than used in this study and can develop research instruments that do not only refer to the indicators that have been used.